Cost estimation model for earthquake damage repair in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Construction at Massey University, Albany, New Zealand - Kahandawa Appuhamillage, Ravindu Visal Dharmasena Kahandawa (Massey University, 2021)
Earthquakes are natural hazards that can devastate nations, their people and the surrounding built environments. Designing a suitable strategy for rapid recovery requires an accurate damage assessment process for the built environment. Loss estimation models were developed to predict the cost of repair, but these models were not used to estimate the costs of post-earthquake repair. This could be due to the fact that these probability-based models tend to provide less accurate outputs. In fact, there is no existing literature on post-earthquake repair cost estimation models that can rapidly produce repair cost estimates. This research developed a post-earthquake cost estimation model for earthquake damage repair work (referred to as a cost of damage repair, earthquake estimation model or C-DREEM). The research used an exploratory sequential research design that used semi-structured interviews (N=19) with engineers, quantity surveyors and builders with experience in earthquake damage repair work as the primary data collection. Then a web-based survey questionnaire (N=310 distributed, N=92 received) of professionals with experience in cost estimation for earthquake damage repair work was the second data collection. The collected data was analysed using thematic analysis, descriptive statistics and non-parametric tests. Based on the findings in the literature, document review and research data analysis, a cost of damage repair earthquake estimation model (C-DREEM) was developed. The C-DREEM model was then validated through a focus group interview session with participants who had experience in the cost estimation for earthquake damage repair work in New Zealand (N=9). Key findings identified from the research were: (i) 11 factors have a critical impact on the accuracy of cost estimation of earthquake damage repair work (CEEDRW) which includes consequential damage, initially unforeseen damage, and changes to the final repair state; (ii) Use of a unit rate and lump sum amount methods were some of the most suitable ways incorporate these factors to CEEDRW; (iii) detailed damage evaluation reports are the most likely information sources post-earthquake for CEEDRW; and (iv) the standardised and automated cost estimation model, C-DREEM, developed by this research can improve both pre and post-earthquake CEEDRW process with include the benefits of sharing consequence functions and probable damage information with probability-based methods. The key contribution to knowledge from this research is identifying the factors affecting CEEDRW, evaluating the significance, selecting methods to incorporate the factors into the costing process, and creating the C-DREEM costing process that combines the pre-and post-earthquake loss estimation processes. The research also supports the professional practice by providing: a standardised and automated cost estimation process; specifying the areas that should be improved, such as the damage reporting process; and a better cost control and monitoring process through standardised rates. Through the findings of the research, government and insurance companies: can standardise and improve the accuracy and speed CEEDRW process, and makes informed decisions to manage the impact of the eleven factors affecting CEEDRW identified by this research.
Keywords: Buildings; Repair and reconstruction; Estimates; New Zealand; Earthquake effects; Costs; Mathematical models; automation; buildings; cost estimation; damage estimation; earthquakes; post-disaster; reconstruction; repair work; 330299 Building not elsewhere classified